The Impact of Brand Image Modiation on the Influence of Relationship Marketing on Customer Loyalty - Kuncoro, Amin (Global Health Science Group, 2024)
The aim of the research is to analyze relationship marketing on customer loyalty mediated by brand image. The research design uses quantitative descriptive using primary data sources taken directly from respondents via questionnaires. The research sample of Herbalife customers in Kodya Semarang with a minimum subscription period of 1 year amounted to 157 respondents. The research results explain that relationship marketing influences customer loyalty, while brand image is able to mediate. However, there is an obstacle, namely that respondents who are outside the Semarang Municipality cannot be used as samples so the results cannot be generalized.